Концептуальні засади створення експертної аналітично-інформаційної підсистеми аналізу ризиків державної системи моніторингу довкілля - Лисиченко, Г.В.; Хміль, Г.А. (Моделювання та інформаційні технології, 2009)
Conceptual bases of creation of expert analytically-informative subsystem of analysis of risks and prognoses estimations of the state of objects of environment of the state system of monitoring of environment are expounded in the article.